2023
DOI: 10.1371/journal.pone.0280488
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiopoietin-1 and -2 levels in human vitreous are associated with proliferative diabetic retinopathy

Abstract: Background Diabetic retinopathy is a frequent complication of diabetes mellitus and a leading cause of blindness in adults. The objective of this study was to elucidate the diabetic retinopathy pathophysiology in more detail by comparing protein alterations in human vitreous of different diabetic retinopathy stages. Methods Vitreous samples were obtained from 116 patients undergoing pars plana vitrectomy. Quantitative immunoassays were performed of angiogenic factors (VEGF-A, PIGF, Angiopoietin-1, Angiopoiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…It has previously been reported that IL-8 is higher in adolescents with T1D and poor metabolic control, possibly providing explanation to this observation [ 43 ]. Furthermore, IL-1β and IL-8 were recently reported to be elevated together in the vitreous fluid of patients with diabetes and proliferative retinopathy [ 44 ]. Several studies report a role for GAL-1 in diabetic retinopathy, and it is possible that our observation is indicative of a shared regulation for IL-1β and IL-8 and GAL-1 in the microvascular pathophysiology of T1D [ 34 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that IL-8 is higher in adolescents with T1D and poor metabolic control, possibly providing explanation to this observation [ 43 ]. Furthermore, IL-1β and IL-8 were recently reported to be elevated together in the vitreous fluid of patients with diabetes and proliferative retinopathy [ 44 ]. Several studies report a role for GAL-1 in diabetic retinopathy, and it is possible that our observation is indicative of a shared regulation for IL-1β and IL-8 and GAL-1 in the microvascular pathophysiology of T1D [ 34 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faricimab-svoa is a heterodimeric bispecific monoclonal antibody developed using CrossMab technology that targets both VEGF-A and Ang2 [173]. CrossMab technology enables correct antibody light chain association with their respective heavy chain and thus enforcing specific heterodimerization of two different antigen binding domains [166,174].…”
Section: Combination Therapy Of Anti-ang2 and Anti-vegfmentioning
confidence: 99%
“…1.1.1. The Role of H. pylori/MetS-Related Pericyte Dysfunction Pathologies and Their Potential Impact on Pregnancy and Neonatal Outcomes Pericytes, which are implicated in H. pylori/MetS-related AH and T2DM pathophysiology [36,37], are specialized cells closely associated with the vasculature system, playing a key role in regulating endothelial cell characteristics and ensuring the constancy and preservation of blood vessels essential for normal vascular functionality [38]. The collaboration between endothelium and pericytes is critical for appropriate microvascular development, constancy, and maintenance [39,40].…”
Section: Potential Impact Of H Pylori/mets On Pregnancy and Neonatal ...mentioning
confidence: 99%